2019
DOI: 10.2116/analsci.19p204
|View full text |Cite
|
Sign up to set email alerts
|

Unique Anion-exchange Properties of 3,3′-Diaminobenzidine Resulting in High Selectivity for Rhodium(III) over Palladium(II) and Platinum(IV) in a Concentrated Hydrochloric Acid Solution

Abstract: The effective recovery of Rh(III) from mixtures also containing Pd(II) and Pt(IV) is one of the most difficult tasks in platinum group metal refining. Adding 3,3′-diaminobenzidine (DAB) to 7 and 10 M HCl aqueous solutions containing Rh(III), Pd(II), and Pt(IV) chlorido species affords the effective separation of Rh(III) from Pd(II) and Pt(IV) through a process where Rh(III) becomes sequestered into solid phases composed of DAB. The stoichiometry and inner coordination sphere of the metal in Rh-DAB complexes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…To increase the efficiency of separation, it is desirable to develop effective separation resins for Pu(IV), as well as other resins for metal ions. [8][9][10][11][12] Microbial metabolite desferrioxamine B (DFB), a trihydroxamate-based siderophore produced by the actinobacteria Streptomyces pilosus, has a very strong chelating ability for many high-valence ions under certain conditions. [13][14][15] For instance, it has been reported that DFB chelates with Pu(IV), 13,14 Am(III), 16 Cm(III), 17 and U(VI) 15 in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the efficiency of separation, it is desirable to develop effective separation resins for Pu(IV), as well as other resins for metal ions. [8][9][10][11][12] Microbial metabolite desferrioxamine B (DFB), a trihydroxamate-based siderophore produced by the actinobacteria Streptomyces pilosus, has a very strong chelating ability for many high-valence ions under certain conditions. [13][14][15] For instance, it has been reported that DFB chelates with Pu(IV), 13,14 Am(III), 16 Cm(III), 17 and U(VI) 15 in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…The noble metals complexes have a specific tendency to create ion pairs with ion exchangers, according to: [MCl 6 ] 2− > [MCl 4 ] 2− >> [MCl 6 ] 3− > aquacomplexes. In accordance with this series, rhodium is the last one to undergo the ion exchange process, hence its low sorption yields in the experiments [21,22].…”
Section: Determination Of the Sorption Yield Depending On The Number Of Process Stepsmentioning
confidence: 60%
“…At relatively high HCl concentrations (>1 mol dm À3 ), anionic Rh chloride complexes [RhCl x (H 2 O) 6Àx ] 3Àx (x ¼ 4-6) are the major species present and some binuclear complex [Rh 2 Cl 9 ] 3À has been also reported. [6][7][8][9] Recovery of anionic Rh complexes from acidic leachates has been investigated by separation methods including cementation, 10 calcination, 11 precipitation, [12][13][14] adsorption, [15][16][17] solid-liquid extraction, 18 liquid-liquid extraction, 19,20 and membrane transport. 21 Among these methods, liquid-liquid extraction (also called solvent extraction) has been widely used as an analytical separation method in laboratories and as a rening methods in industries owing to advantages, such as ease of scale-up and the possibility of continuous operation.…”
Section: Introductionmentioning
confidence: 99%